2014
DOI: 10.7866/hpe-rpe.14.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Tax Compliance Costs: A Review of Cost Burdens and Cost Structures

Abstract: SummaryOur paper provides a comprehensive report of empirical research on tax compliance costs. Compared to previous reviews, our focus is on average costs for sub-groups (individual taxpayers, small businesses, large businesses) and the composition of the cost burden with regards to different cost components (in-house time effort, external adviser costs, other monetary expenses), different taxes (e.g. income tax, value added tax) and different activities like tax accounting and tax planning. In addition, we g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 62 publications
1
3
0
1
Order By: Relevance
“…First, non-disclosing firms are smaller, on average. This fits well with the finding of the literature that the compliance costs of taxes and bookkeeping have large economies of scale (see the review of Eichfelder and Vaillancourt 2014 ). Therefore, smaller firms have a stronger incentive to reduce compliance costs by simplifying financial reporting.…”
Section: Methodssupporting
confidence: 90%
“…First, non-disclosing firms are smaller, on average. This fits well with the finding of the literature that the compliance costs of taxes and bookkeeping have large economies of scale (see the review of Eichfelder and Vaillancourt 2014 ). Therefore, smaller firms have a stronger incentive to reduce compliance costs by simplifying financial reporting.…”
Section: Methodssupporting
confidence: 90%
“…It adds up to additional costs in professional fees, audit fees, consultation charges etc. (Eichfelder & Vaillancourt, 2014; Hanefah et al, 2002; Sandford et al, 1989). A comparative study done in Australia by (Pope & Mohdali, 2010; Tran-Nam, 2000) observed that under the GST tax regime, tax compliance cost is higher in comparison to the VAT and sales tax system.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…There have been various discussions as to what constitutes compliance cost (Ariff & Pope, 2002;Blaufus & Hoffmann, 2020;Blaufus et al, 2019;Eichfelder & Hechtner, 2018;Eichfelder & Vaillancourt, 2014;Lignier & Evans, 2012;Sapiei, 2012;Schutte & Van der Zwan, 2019), the measurement of these costs (Shaw et al, 2008), and conceptual issues (Tran-Nam et al, 2000). The challenges facing TCC research have to do with how TCC should be defined and how to measure it (Sapiei, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%